Effect of human pharmaceuticals common to aquatic environments on hepatic CYP1A and CYP3A-like activities in rainbow trout (Oncorhynchus mykiss): An in vitro study. (August 2018) - Burkina, Viktoriia; Sakalli, Sidika; Pilipenko, Nadezhda; Zlabek, Vladimir; Zamaratskaia, Galia
Abstract: This study examined the ability of several human pharmaceuticals to modulate hepatic piscine CYP-mediated monooxygenase activities. Effects of six pharmaceuticals: diclofenac, sulfamethoxazole, tramadol, carbamazepine, venlafaxine and nefazodone, were investigated in vitro in rainbow trout hepatic microsomes. The reactions of 7-ethoxyresorufin-O-deethylase (EROD) and benzyloxy-4-trifluoromethylcoumarin-O-debenzyloxylase (BFCOD), were used as markers for hepatic CYP1A and CYP3A-like activities, respectively. Our results showed that EROD and BFCOD activities were both affected by nefazodone. Nefazodone inhibited EROD in a dose dependent manner and was found to be a potent non-competitive inhibitor of EROD with a Ki value of 6.6 μM. BFCOD activity was inhibited non-competitively in the presence of nefazadone with Ki value of 30.7 μM. BFCOD activity was slightly reduced only by the highest concentration of carbamazepine. Diclofenac, sulfamethoxazole, tramadol, and venlafaxine did not affect the activity of either EROD or BFCOD. We further exposed microsomal fraction to mixtures of six pharmaceuticals to investigate potential inhibition. The results showed that EROD and BFCOD activity was inhibited on 94% and 80%, respectively at higher tested concentration. To our knowledge, this is the first report to demonstrate an inhibitory effect of nefazodone on hepatic CYP1A and CYP3A-like proteins in rainbow trout. Graphical abstract: Image Highlights: The inhibitory potency of six medicines on rainbow trout liver microsomes was studied. Two CYP mediated reaction were measured: EROD and BFCOD. Nefazodone inhibited EROD and BFCOD in a non-competitive manner. Neither single nor mixture of six pharmaceuticals inhibit enzyme activity at environmentally relevant concentrations. Mixture of all compounds exhibit inhibition pattern at 10 and 100 μM.